Analisis Pengaruh Variasi Diameter Pelat Helical Terhadap Daya Dukung Pondasi Helical Pada Tanah Gambut - Adi, Sapria; Fatnanta, Ferry; Satibi, Syawal (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Application of helical pile to support structures constructed over peat is still a new method. Moreover, helical pile can provide an alternative to wood pile. The research is necessary to develop this foundation. There were 6 different helical piles, wood pile, and plain pile embedded in peat. Every pile was under static axial compressive load based on constant rate of penetration procedure. The test results show that, load-settlement curves of helical piles behave in ways that show end bearing. According to the curve, helical piles with 2 and 3 plates using diameter of bottom plate at least 25 cm can carry greater load compared to wood piles at same settlement. Helical pile with only one plate is not effective to replace wood pile. Their bearing capacity are not much different relatively. Based on interpretation result, helical pile with two plates has greater ultimate bearing capacity than three plates. The difference of ultimate bearing capacity is caused by the diameter size of bottom helical plate. The bigger diameter of helical plate is attached, the greater ultimate bearing capacity is.Keywords: Helical Pile, Plate Diameter, Peat, Bearing Capacity, Wood Pile